2021
DOI: 10.1080/21655979.2020.1863618
|View full text |Cite
|
Sign up to set email alerts
|

Production of L-carnitine-enriched edible filamentous fungal biomass through submerged cultivation

Abstract: The edible filamentous fungi are hot candidate for future supply of functional food and feed with e.g. protein, essential amino acids, and compounds with immunostimulant activity. L-carnitine that plays a crucial role in energy metabolism represents a functional compound normally produced by Zygomycetes filamentous fungus Rhizopus oligosporus in solid-state fermentation. The present study provides the first insights on production of L-carnitine-enriched edible fungal biomass through submerged cultivation of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 46 publications
2
24
1
Order By: Relevance
“…In the present study, we examined the effect of the culture conditions, two different media, and supplementation of the media on the level of free L-carnitine in the biomass of Y. lipolytica strains. The results con rm other ndings [7,22,[35][36][37][38] revealing that the fermentation process parameters can have a signi cant impact on improvement of the nutrient content in the biomass of the studied yeast strains. However, we showed that the concentration of free L-carnitine in the yeast biomass depended primarily on the medium used, and, to some extent, on the strains and culture conditions.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…In the present study, we examined the effect of the culture conditions, two different media, and supplementation of the media on the level of free L-carnitine in the biomass of Y. lipolytica strains. The results con rm other ndings [7,22,[35][36][37][38] revealing that the fermentation process parameters can have a signi cant impact on improvement of the nutrient content in the biomass of the studied yeast strains. However, we showed that the concentration of free L-carnitine in the yeast biomass depended primarily on the medium used, and, to some extent, on the strains and culture conditions.…”
Section: Discussionsupporting
confidence: 87%
“…The standard laboratory YPD medium, used in this study as supplementary, contains yeast extract with only 0.10%-0.15% of fatty acids. Yeast extract is mainly added to the medium as a nitrogen source; however, it also contains several biocomponents, including su cient amounts of carnitine, to complement the carnitine requirements of yeast [4,7]. It was reported that the effect of yeast extract on Lcarnitine biosynthesis was dissimilar among tested fungal strains.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations